2011
DOI: 10.1002/glia.21178
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor p53 influences microglial activation phenotype

Abstract: Several neurodegenerative diseases are influenced by the innate immune response in the central nervous system (CNS). Microglia, have pro-inflammatory and subsequently neurotoxic actions as well as anti-inflammatory functions that promote recovery and repair. Very little is known about the transcriptional control of these specific microglial behaviors. We have previously shown that in HIV associated neurocognitive disorders (HAND), the transcription factor p53 accumulates in microglia and that microglial p53 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 69 publications
(94 reference statements)
5
59
0
Order By: Relevance
“…9 Upregulation of proinflammatory genes induced by interferon gamma was suppressed in p53 Ϫ/Ϫ microglia. 21 These findings indicated that p53 is also involved in endothelial cell injury and microglia activation after brain damage. We found that HI-induced upregulation of p53, BBB damage and microglia activation were attenuated by moderate DR. Inhibiting p53 decreased BBB damage and microglia activation in NL-HI pups, Figure 6.…”
Section: Tu Et Al Moderate Dr and Neurovascular Damage 495mentioning
confidence: 91%
“…9 Upregulation of proinflammatory genes induced by interferon gamma was suppressed in p53 Ϫ/Ϫ microglia. 21 These findings indicated that p53 is also involved in endothelial cell injury and microglia activation after brain damage. We found that HI-induced upregulation of p53, BBB damage and microglia activation were attenuated by moderate DR. Inhibiting p53 decreased BBB damage and microglia activation in NL-HI pups, Figure 6.…”
Section: Tu Et Al Moderate Dr and Neurovascular Damage 495mentioning
confidence: 91%
“…The expression and activity of p53 increases in microglia in response to cellular stress, DNA damage, and oxidative stress (78)(79)(80). In postmortem brain tissues from patients with HIV-associated dementia (HAD) elevated levels of p53 were particularly prominent in the microglia (78,81). HIV-infected p53-deficient neuron/microglia cocultures showed increased neuronal survival compared with WT (78).…”
Section: R E V I E W S E R I E S : G L I a A N D N E U R O D E G E N mentioning
confidence: 99%
“…Exposing neural cultures to HIV-gp120 coat protein induces robust p53 activation and co-culture studies of cells from p53 knockout mice demonstrate that both neurons and microglia must express p53 for gp120-induced neurotoxicity (Garden et al, 2004). While p53 activity in neurons may promote activation of apoptotic cascades, the role of p53 in microglia appears more nuanced, promoting proinflammatory behaviors and suppressing microglia functions that might provide neurotrophic effects (Jayadev et al, 2011; Mukerjee et al, 2010). Exposing cultured astrocytes to Vpr leads to p53 activation and induction of downstream apoptotic pathways mediated by caspase-6 (Noorbakhsh et al, 2010).…”
Section: Microglia P53 and Hiv-associated Neurocognitive Disordersmentioning
confidence: 99%